Improving Competitive Advantage - Leech, Corinne (Elsevier Limited, 2004)
The new edition of the Chartered Management Institute's Open Learning Programme has been updated to include the latest management concepts and methodologies. It includes current management concepts, the changing legal framework in which managers operate and the impact of technology in the work environment. The scope of the workbooks has been broadened to enable more generic and stand-alone use of the materials. Each workbook has a new introduction that places the subject area within the context of the managerial role and the end of each section now has a learning summary